Animals on the edge : reporting from the frontline of extinction - Weston, Christopher (Thames & Hudson, 2009)
Chris Weston and Art Wolfe are among the finest wildlife photographers at work today as well as being passionate advocates of wildlife conservation. This book features their stunning photographs of some sixty rare and endangered mammals across six continents, from the High Arctic to rain forest, steppe, and desert. The chapters are organized by region, and the photo captions detail each animal’s habits, habitat, and conservation status. In his concise, compelling reports, Weston goes behind simplistic headlines of good versus evil, of innocent creatures assailed by greedy, selfish humans. Instead he investigates all sides of the story, talking to villagers, officials, scientists, poachers, hunters, and conservation workers. What becomes powerfully clear is the need for solutions that work for people as well as animals. The reasons that animals are endangered are many—from habitat destruction and illegal hunting to global warming—but there is one common factor: the conflict between animals and people sharing the same piece of land is intensifying.